Impact of Migration on Poland EU Mobility and Social Change (University College London, 2018)
How has the international mobility of Polish citizens intertwined with other influences to shape society, culture, politics and economics in contemporary Poland? The Impact of Migration on Poland offers a new approach for understanding how migration affects sending countries, and provides a wide-ranging analysis of how Poland has changed, and continues to change, since EU accession in 2004. The authors explore an array of social trends and their causes before using in-depth interview data to illustrate how migration contributes to those causes. They address fundamental questions about whether and how Polish society is becoming more equal and more cosmopolitan, arguing that for particular segments of society migration does make a difference, and can be seen as both leveller and eye-opener. While the book focuses mainly on stayers in Poland, and their multiple contacts with Poles in other countries, Chapter 9 analyses 'Polish society abroad', a more accurate concept than 'community' in countries like the UK, and Chapter 10 considers impacts of immigration to Poland. The book is written in a lively and accessible style, and will be important reading for anyone interested in the influence of migration on society, as well as students and scholars researching EU mobility, migration theory and methodology, and issues facing contemporary Europe.